Relationship between speed and leg muscle explosive power with long jump results Pasi athlete Indragiri Hilir - rizal, khairul; antoni, prima (FKIP Universitas Islam Indragiri, 2023)
This study aims to determine the relationship between speed and leg muscle explosive power in the long jump of Pasi Indragiri Hilir athletes. This type of research is correlational, where correlation analysis is to find the magnitude of the influence or relationship between variables, the independent variables (X1) and (X2) on the dependent variable (Y). The population in this study were all PASI Indragiri Hilir athletes with a total of 10 athletes. Meanwhile, the sampling in this study used a total sampling technique with a total of 10 athletes. To obtain research data, tests and measurements were carried out, namely the data analysis technique used was multiple product moment correlation. From the research results, the correlation coefficient rx1y = 0.969 ≥ rtable = 0.765 (the research hypothesis is accepted) and the significant correlation test of the t distribution shows (tcount = 8.492) ≥ (ttable = 2.306) then Ho is rejected and Ha is accepted (Significant). From the research results, it was found that the correlation coefficient rx2y = 0.982 ≥ rtable = 0.765 (the research hypothesis is accepted) and the significant correlation test of the t distribution shows (tcount = 13.93) ≥ (ttable = 2.306) then Ho is rejected and Ha is accepted (Significant). From the research results obtained multiple correlation rx1x2 = 0.589 (rejected research hypothesis) and significant testing of the correlation of the t distribution shows (tcount = 2.055) ≥ (ttable = 2.306) then Ho is accepted and Ha is rejected then, (not significant). Double correlation coefficient test rx1x2y = 0.934 ≥ rtable = 0.765 (Research hypothesis accepted) and significant correlation testing F test shows (Fcount = 8.302) (Ftable = 4.74) then Ho is rejected and Ha is accepted (Significant). This means that by increasing the speed and explosive power of the leg muscles, it turns out that the long jump results can be increased. From the results of the study, it was concluded that there was a significant relationship between speed and explosive power of the leg muscles together in the results of the long jump in PASI Indragiri Hilir athletes.